The relationship between the development and use of teaching and learning support materials: the case of "A year of special days" booklet - Urenje, Shepherd (Rhodes University, Faculty of Education, Department of Education, 2006)
This research is an interpretive case study, which investigated the relationship between the development and use of the teaching and learning support material, "A Year of Special Days" . An in depth investigation was conducted in South Africa and Zimbabwe where developers and users of the booklet were asked to contribute their experiences with the booklet through questionnaires, semi-structured interviews and workshops. Developers contributed on the purpose for which the booklet was produced while the users explained how the booklet was being used in different contexts. The research also tracked the development and use of booklet in the Southern African Development Community (SADC) region through a workshop held at the Environmental Education Association of Southern Africa (EEASA) Conference in Lusaka, Zambia, in May 2005. Some personal interviews and informal encounters with people who have used it in the past and those using it now were also conducted at EEASA. This case study explored the axes of tension between the development and use of the resource material, "A Year of Special Days" , with the view to informing development and use of materials at the SADC Centre. A long-term intention is to use the framework developed, for similar work in the wider SADC region. The research recommended on how the SADC Centre can track the relationship between the materials developed at the Centre and their use in different contexts. The study established that the booklet "A Year of Special Days" was initially developed for informal education by faith communities mainly in the Anglican Church but turned out to be a resource more applicable for formal education mainly in the national school system of South Africa for environmental learning. That the resource material lacked effective monitoring support from the developers for the initial intended users where there was no formal education structure was an important link in materials development. It is important for resource materials developers to facilitate the participatory monitoring and evaluation of resource materials when they are in use. The study also established that SADC resources materials are easily adaptable and that the process of resource materials development offers important networking opportunities, which allow the adaptation and adoption of similar resource materials for local contexts. The booklet was adapted and adopted by at least eight countries in the form of a booklet, a calendar or a poster. This study provides some recommendations that may be used to guide the Southern African Development Community Regional Environmental Education Programme (REEP) to enhance processes in the development and adaptation of teaching and learning support materials by environmental educators in southern Africa.
Keywords: Southern African Development Community Teaching -- Aids and devices -- South Africa; Environmental education -- South Africa -- Case studies; Environmental education -- Curricula -- South Africa